Determinants of e-wallet acceptance among west Malaysian low-income group: attitude as a mediating role / Rohaiza Kamis - Kamis, Rohaiza (2024)
The popularity of electronic wallets (e-wallets) aligns with the global trend of cashless payment solutions, attracting significant attention due to their potential to enhance individual well-being and foster business growth. However, e-wallet acceptance, especially among the Malaysian low-income group, remains relatively low despite a variety of government initiatives and programmes underway to promote the use of electronic wallets. Therefore, this study aims to examine the determinants of e-wallet acceptance among the low-income West Malaysian population. Drawing on Technology Acceptance Model (TAM) and a review of previous studies, an integrated conceptual framework was developed. This framework comprises one (1) dependent variable (e-wallet acceptance), five (5) independent variables (perceived ease of use, security, government intervention, social influence, trust), with attitude serving as a mediator. Data were collected from 265 low-income earners in West Malaysia through a web-based self-administered survey. Eligible respondents possessed e-wallet experience and a household monthly income of less than RM4,850. Prior to the main data collection, a pilot survey was conducted to test the instrument's final version, and the scale reliability was assessed using the coëfficiënt alpha (a), item-to-total correlation, and exploratory factor analysis (EFA). Bef ore proceeding to the measurement model, a normality test, and a common method variance (CMV) test were performed. For data analysis, partial least square equation structural modelling (PLSSEM) was applied. The findings revealed a positive relationship between perceived ease of use (PEOU), trust (TR), and attitude (ATT) towards e-wallet acceptance (eWA). In addition, it was proven the role of attitude (ATT) as a mediator for perceived ease of use (PEOU), social influence (SI), and trust (TR) with e-wallets acceptance (eWA); but not for security (SC) and government intervention (GI). In contrast, security (SC), government intervention (GI), and social influence (SI) portrays to have no significant towards e-wallet acceptance. The study offers valuable insights that can encourage both e-wallet providers and regulators to improve the quality of e-wallet services. Acknowledging the existence of certain limitations, this study suggests future research endeavours consider the provided suggestions to further enrich our understanding of this domain.